The Role of The Emotional Component in The Structure of Adolescents’ Independence as a Condition of Their Personal Growth - Polishchuk, Daria (Journal of History Culture and Art Research, 2021)
The article presents material on the importance of independence as a condition for personal growth of adolescents. Latest research on the development of adolescents’ independence are analyzed. The development of the emotional component in the structure of adolescents’ independence, which is characterized by such criteria as self-esteem and anxiety, is considered. The prevalence of low self-esteem in girls has been established, which can lead to dependence on other people’s opinions, self-doubt, depression and apathy. The boys have a predominance of a very high level of self-esteem, which can have negative consequences in the form of refusal to work on their further personal development and problems in relationships with others. A sharp drop in confidence at the end of adolescence was found. It is associated with the irreversibility of awareness of the end of childhood and taking full responsibility for the acts of adolescents. It is also determined that modern adolescents have a low level of anxiety. That means, that they do not feel emotional discomfort, which is associated with the expectation of a threat. But it could also mean that there was the presence of protective mechanisms and reluctance to talk about this topic. The importance of independence development in adolescence is showed.